Analysis of the Impact of Usury Practices on Economic Stability from an Islamic Perspective - Nisa, Chairun; Hamidah, Nazala Zalfa; Kusumawati, Nabila Dhea; Taufikurrahman, Taufikurrahman (Islamic Micro Finance Journal, 2024)
This article examines the usury (riba) concept from an Islamic perspective and its implications for economic systems and social life. Riba, which means "excess" or "addition," is prohibited in Islamic teachings as it is considered a form of injustice and exploitation. Through an analysis of Quranic verses and Hadith, the article explains the theological and moral foundations behind the prohibition of riba. It also explores various types of riba, including riba nasiah (interest on loans) and riba fadl (unequal exchange of similar goods), as well as their impact on individuals and society. In the modern context, the article highlights the challenges Muslims face in avoiding riba amidst a global financial system dominated by interest. Proposed solutions include strengthening Islamic financial systems and educating communities on the importance of fair and riba-free transactions. This study aims to raise awareness about the dangers of riba and promote the implementation of Islamic economic principles in daily life